Pengaruh Intellectual Capital Terhadap Kinerja Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021 - Moh Hasan Ramdana M; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the influence of Intellectual Capital on the Performance of Companies incorporated in companies listed on the Indonesia Stock Exchange. In this study, a sampling technique was determined using purposive sampling, and based on predetermined criteria, the number of samples was 85 companies during 2019-2021. This study used multiple linear regression analysis. The results show that Intellectual Capital: Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA) has a positive effect on Return On Asset (ROA).Keywords: Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA) and Return on Assets (ROA)